A qualitative inquiry into the issues of information content of analysis’s report: Evidence from Malaysia - Mohd Thas Thaker, Hassanudin; Mohamad, Azhar; Omar, Azura; Mustaffa Kamil, Nazrol Kamil; Duasa, Jarita (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2017)
Analyst report is one of the reference sources available to investors in enhancing their decision-making process of investment. Analyst report plays a significant role in recommending shares and disseminating market information to the investor. However, in the context of Malaysia, the analyst report tends to over-rely on quantitative information and statistical analyses in producing recommendations to investors. As a result, analyst report is deemed to have less predictive power from investors’ perspective. Using a semi-structured interview, we investigate the informational content of analyst report in Malaysia by conducting an in-depth interview with six respondents from institutional and retail investors. The findings from the interview reveal that the analyst report in Malaysia tends to disclose information based on simple statistical analyses to formulate recommendations, and tends to ignore other significant qualitative information. This study adds to the current literature by proposing an adaption of both quantitative and qualitative information as the mode of informational disclosure in the analyst report.